Sustainable Decision-Making: Non-Monetary Incentives for Pro-Social Behavior in the Energy Sector - Stephanie Rosenkranz; Katrin S. Muehlfeld; G. van der Laan; Gustav U. Weitzel; J. van der Donk; H. Ivanova; E.J. van Kesteren; M. Ottink; H. van der Spek (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2013)
Taking into account insights into the reality of human decision-making, is an important challenge for today's policymakers. Are there `cheaper, more efficient and possibly as well more effective, non-financial ways of influencing the behaviour of private and corporate citizens, nudging them towards socially desired choices, for example, in the domain of energy consumption? Can such mechanisms complement or substitute for monetary incentives in fostering sustainable decision-making in policy relevant areas such as energy consumption? If so, what mechanisms might be feasible to implement in actual policymaking? Against this background, the Dutch Ministry of Economic Affairs (Ministerie van Economische Zaken) wants to know which "nudges" are the most suitable for application in the field of energy conservation. To this end, in this report we (1) take stock what is known about the effects of non-monetary incentives in general, and legacy reminders in particular, in increasing individuals' regard for collective interests and for intergenerational beneficence, in particular in the domain of energy consumption (literature review); (2) investigate in a laboratory setting the effects of selected non-monetary incentives on a selection of relevant decision tasks (laboratory experiments); and (3) apply the insights from the literature review and laboratory experiments to specific instruments of policy-making in the Netherlands.
Keywords: 330; Behavioral Economics; Choice Architecture; Nudge; Energy Efficiency